Deciphering the Role of Dendritic Cells in the Regulation of Allergic Asthma: A Comprehensive Review - Meera Kumari; Mohd Aftab Siddiqui (Journal of Bio-X Research)
Dendritic cells (DCs) are critical for initiating and regulating immune responses, including responses in allergic asthma; they are traditionally divided into subgroups based on surface markings, function, and origin. In allergic asthma, DCs stimulate and activate T helper 2 cells during the generation of cytokines such as interleukin-4 (IL-4), IL-5, and IL-13, which promote allergic inflammation with airway hyperresponsiveness. However, recent research has highlighted the existence of DC subsets with immune regulatory properties that can counteract allergic reactions and promote tolerance. These regulatory DCs induce regulatory T-cell reactions and suppress effector T-cell reactions, thereby maintaining immune homeostasis and preventing excessive inflammation. The recognition and description of these immunoregulatory DC subsets are essential for the improvement of new therapeutic strategies for allergic asthma. Targeting specific signaling pathways involved in DC-mediated immune regulation could open new avenues for therapeutic interventions. Additional research is necessary to elucidate the particular mechanisms underlying the function and potential of DC subsets as therapeutic targets.